IMPROVING THE EFFECTIVENESS OF TREATMENT OF PATIENTS WITH KNEE INJURIES (Conferencea, 2024)
Knee injury is one of the most common injuries, due to the high load on this segment and its anatomical features. Most injuries are mild, occur in everyday life (for example, when falling on the street) and are subject to outpatient treatment in the emergency room. In addition, the knee joint often suffers during various sports, while the severity and nature of injuries can vary greatly.